Análise etofarmacológica de um novo teste de interação presa-predador : o teste de exposição ao rato - Campos, Kelciane Caetano Ferreira de (Universidade Federal de São Carlos, 2013)
The rat exposure test (RET) is a new ethological model of predator-prey with interactions between the rat and the mouse. The RET allows the expression of defensive behaviors in the prey. The experimental apparatus is constituted by an exposure chamber divided into two equal-sized compartments (the surface and the predator compartment) by a wire mesh screen. Although previous studies have used the RET as an animal test of anxiety, there are not reports in literature showing which emotional dimensions the test elicits in the mouse. Yet, it remains to be investigated the predictive validity of the RET. Therefore, this study sought to identify distinct emotional dimensions through the factorial analysis of the behavioral measures exhibited by mice in the RET. In addition, we investigated the effects of pro- and antiaversive drugs on behavior of mice exposed to this ethologically based test. The factorial analysis showed (i) a component of locomotor activity, expressed by the frequency of entries into the three compartments; (ii) that the behavioral measures displayed in home chamber and tunnel loaded on the same factor, suggesting that represent similar emotional profile, and therefore they were grouped into the protected compartment, differing from those displayed in the surface (unprotected compartment) and (iii) a component to assess defensive behavior [time spent in the protected area and risk assessment (e.g., stretched attend postures) in the protected area]. The pharmacological validation of the RET was carried out by intraperitoneal (i.p.) injections of drugs acting at GABA/benzodiazepine receptor complex (diazepam and alprazolam), serotonin system (buspirone, 8-OHDPAT, SDZ SER 082 and MK-212), caffeine and yohimbine, as well as with acute and chronic (21 days) treatment with antidepressants (fluoxetine and imipramine). Interestingly, while alprazolam and fluoxetine (chronic) attenuated the defensive behavior, caffeine and fluoxetine (acute) facilitated the exhibition of defensive behaviors in mice exposed to the rat. Based on the anti-aversive effects observed with the potent benzodiazepine agonist alprazolam and with the antidepressant fluoxetine (chronic), the RET seems to be a useful test to evaluate the effects of drugs commonly used in the treatment of panic disorder.
Keywords: Ansiedade; Interação presa-predador; Mecanismo de defesa; Psicofarmacologia; Análise fatorial; CIENCIAS BIOLOGICAS::FISIOLOGIA